A brief review of the efficacy in artificial intelligence and chatbot-generated personalized fitness regimens - Bays, D. K.; Verble, C.; Powers Verble, K. M. (Strength and Conditioning Journal, 2024)
Artificial intelligence (AI) and chatbot technologies have rapidly emerged with promising applications in public health, including developing personal lifestyles and exercise routines. This article examines the effectiveness of AI-based chatbot platforms to generate personalized exercise regimens. Chatbots are freely accessible to users with Internet access and may be more cost-effective than a personal trainer. This review highlights multiple examples of AI being used to offer fitness advice, supplement athletic coaching, and create everyday exercise routines. The results of these studies demonstrate a positive outlook on using AI for strength and conditioning applications, for personal and professional use. Despite having the potential to replace personal fitness trainers for everyday users and athletes alike, more extensive research should be performed using AI combined with physicians, personal trainers, and nutritionists to determine areas where AI can be further optimized. More research focusing on the effectiveness of AI-generated routines for the everyday user may further validate the potential for chatbot-mediated exercise. This brief review aims to evaluate the efficacy of AI-generated personalized fitness regimens, emphasizing physical fitness, athletic performance, and overall physical and mental well-being. The video abstract for this article can be found in the video SDC 1.